Presence and duration of cardiac sounds in healthy horses at high altitude - Arévalo, Ana María (2019)
The presence and duration of cardiac sounds is reported in 24 healthy equines from an area located at 2600 meters above sea level. The data was taken by phonocardiography directly on the precordial area. In all equines, sounds 1 and 2 were identified. Sound 4 was present in 87.5% of equines and sound 3 was detected only in 29.2% of individuals. The study shows the common presence of sound 4 in contrast to the low presentation of sound 3 in healthy horses.